ANALISIS BUDIDAYA LEBAH MADU GALO-GALO DI NAGARI BUKIK KANDUANG KECAMATAN X KOTO DIATAS KABUPATEN SOLOK - Wahyuni, Rizka; Zella, Arie; Zuriyani, Elvi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of developing alternative businesses that are environmentally friendly and sustainable in rural areas, one of which is through the cultivation of Galo-Galo honey bees in Nagari Bukik Kanduang, X Koto Diatas District, Solok Regency. This study was conducted to analyze: 1) The potential of Galo-Galo honey bee cultivation in Nagari Bukik Kanduang, 2) The impact of Galo-Galo honey bee cultivation on the socio-economic conditions of the community, 3) The impact of Galo-Galo honey bee cultivation on the physical environment. The type of research used is a mixed method, which is a combination of quantitative and qualitative approaches. The research was conducted in Nagari Bukik Kanduang, X Koto Diatas District, Solok Regency. Data collection techniques were carried out through observation, documentation, interviews with key informants, and distribution of questionnaires to all Galo-Galo honey bee farmers (using total sampling technique). Quantitative data were analyzed using percentage formulas and the respondent achievement level (TCR), while qualitative data were analyzed through the Miles & Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate: 1) The Galo-Galo honey bee cultivation in Nagari Bukik Kanduang has high potential, supported by natural conditions, vegetation, and community interest. 2) Socio-economically, this cultivation positively impacts income increase and creates job opportunities, although most of it is still a side business. 3) From an environmental perspective, this cultivation contributes to forest conservation and maintaining biodiversity through the role of bees as natural pollinators.